PROBLEMS OF FULFILLMENT OF THE RIGHT TO EXPECT OPINIONS AND VIOLATIONS OF THE RIGHT TO HEALTH IN INDONESIA - Tat Marlina; Duwi Handoko; Riadi Asra Rahmad (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2022)
The purpose of this paper is to find out the problem of fulfilling the right to express opinions and violations of the right to health in Indonesia. This type of research is normative legal research specifically discussing human rights in the field of expressing opinions and rights to health. Data analysis in this study was carried out systematically based on the research problems described qualitatively. In relation to expressing opinions in public, such as demonstrations or demonstrations with many participants, restrictions on freedom are usually associated with